2012
DOI: 10.1590/s0103-84782012000600008
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de água pela cultura do lírio, cultivado em substratos alternativos em condições de ambiente protegido

Abstract: Consumo de água pela cultura do lírio, cultivado em substratos alternativos em condições de ambiente protegido.Ciência Rural, v.42, n.6, jun, 2012. Ciência Rural, Santa Maria, v.42, n.6, p.1001-1006, jun, 2012 ISSN 0103-8478

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
0
4
0
9
Order By: Relevance
“…All substrates produced plants that were different (Table 1) from the advertised height of the 'Diamond' cultivar (15-20cm, SAKATA SEED SUDÁMERICA, 2015). SOARES et al (2012), while working with lilies grown on different substrates, observed increases * Substrate 1=50% soil + 50% rice husk ash, Substrate 2=80% soil + 20% worm castings, Substrate 3=80% rice husk ash + 20% worm castings, Substrate 4=40% soil + 40% rice husk ash + 20% worm castings, Substrate 5=100% peat, Substrate 6=100% Mecplant ® commercial substrate (formed of pine bark, vermiculite, acidity regulator, and fertilizer), and Substrate 7=50% peat + 50% rice husk ash. ** Medium not followed by the same letter in the column differ by Kruskal-Wallis test at 5% probability of error.…”
Section: Resultsmentioning
confidence: 99%
“…All substrates produced plants that were different (Table 1) from the advertised height of the 'Diamond' cultivar (15-20cm, SAKATA SEED SUDÁMERICA, 2015). SOARES et al (2012), while working with lilies grown on different substrates, observed increases * Substrate 1=50% soil + 50% rice husk ash, Substrate 2=80% soil + 20% worm castings, Substrate 3=80% rice husk ash + 20% worm castings, Substrate 4=40% soil + 40% rice husk ash + 20% worm castings, Substrate 5=100% peat, Substrate 6=100% Mecplant ® commercial substrate (formed of pine bark, vermiculite, acidity regulator, and fertilizer), and Substrate 7=50% peat + 50% rice husk ash. ** Medium not followed by the same letter in the column differ by Kruskal-Wallis test at 5% probability of error.…”
Section: Resultsmentioning
confidence: 99%
“…Trigueiro e Guerrini (2003), em estudo avaliando a viabilidade do uso de lodo de esgoto como componente do substrato para produção de mudas de eucalipto, verificaram que os tratamentos com 50% e 60% de lodo de esgoto resultaram em maior massa seca radicular e da parte aérea das mudas, em comparação com outras porcentagens de lodo de esgoto. Clement e Machado (1997) afirmaram que a incorporação de compostos orgânicos nos substratos pode influenciar na produção de biomassa e das raízes de determinadas espécies florestais.…”
Section: Discussionunclassified
“…A razão entre massa seca da parte aérea e raiz é comumente menor em ambiente de baixa fertilidade, podendo ser considerada estratégia da planta para retirar o máximo de nutrientes naquela condição (TEDESCO et al, 1999;CALDEIRA et al, 2000). Então, pode-se inferir que o tratamento-testemunha não proporcionou bom suprimento de nutrientes para as plantas e que os demais tratamentos apresentaram maior teor de nutrientes em razão, principalmente, dos teores de matéria orgânica adicionados pelo lodo de esgoto, casca de arroz carbonizada e palha de café in natura.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O substrato utilizado foi uma mistura de solo+turfa+casca de arroz carbonizada na proporção de 3:1:1 (SOARES et al, 2012). Sabe-se que a casca de arroz serve para dar maior aeração e porosidade ao substrato, enquanto que a turfa contribui para a matéria orgânica.…”
Section: Methodsunclassified